Laser de baixa intensidade na regeneração de nervo isquiático de ratos após tubulização com câmara de silicone - Mendonça, Giselle Bonifácio Neves (2013)
Peripheral nerves are constant targets of traumatic injuries such as crushing and partial or complete sections resulting in decrease or loss of motor function and sensitivity of the innervated area, its severity will depend on the involvement of nervous structures. The worst damage frame is that of total nerve collapse (neurotmesis), which invariably requires surgical treatment. This study aimed to evaluate the morphological and functional effects of rat’s sciatic nerve regeneration after surgical section tubing with silicone chamber and treatment with low-intensity laser (830 nm) in 126 days. We used two groups, control (GC) and laser (GL) with six animals in each. All animals underwent left sciatic nerve neurotmesis followed by tubing with silicone chamber with five mm distance between nerve stumps. Animals in GL received radiation with a wavelength of 830 nm, energy density of 4.13 J/cm², on eight points from the spinal cord to nerve injury site, totaling 40 days of irradiation divided into two distinct periods. The first stage began at the immediate post-operative period where 20 laser applications were performed on alternate days. The second stage occurred 40 days before performing euthanasia in animals submitted to more than 20 days of laser applications on alternate days. During the experiment, we performed functional assessment through the Sciatic Functional Index and Ankle Angle. After 126 days, the animals were euthanized and the fragments of the nerves were removed and fixed in 10% formalin buffered for histological analysis with HE, Luxol Fast Blue and Picrosirius Red staining, and immunohistochemistry with neurofilament antibody (NF), FGF-2 and S-100. Microscopically, we observed the presence of axonal growth, Wallerian degeneration, inflammatory infiltrate and fascicular reorganization. For HE analysis, we stablished descriptive scores and for the other histological data we carried out quantitative analysis through program Image J. In GL we observed better axonal growth, reorganization of issues, absence of inflammatory infiltrate, greater amount of myelin and less collagen, increased expression of S-100 and NF and lower expression of FGF-2. Regarding the function of the sciatic nerve, no functional improvement was observed.